(untitled) (INNOVATIVE ECONOMY, 2024)
Nahirna N.I., Demkura I.T. CLIMATIC CHANGES AS DETERMINANTS OF THE FUNCTIONING OF GLOBAL FOOD SECURITY Purpose. The aim of the article is to substantiate the impact of climate change on the functioning of global food security. Methodology of research. The basis of the study is a systemic and interdisciplinary approach, which covers ecological, economic and social aspects of food security. The following research methods were used to achieve the goal in the article: analysis and synthesis – to study the scientific literature and generalize the theoretical foundations of global food security; historical and logical methods – when analysing the impact of climate change on food security in historical retrospect; dialectical method – when revealing transformational changes in the food system; deduction and induction – when formulating conclusions and generalizations; visualization method – for graphical presentation of research results. Findings. The role of climate change as a global challenge affecting food security is substantiated. Historical periods of food security are characterized and the main determinants for each of them are identified. The role of climatic factors in the formation of the global food system is confirmed. The impact of increasing average temperatures and extreme natural events on food security is revealed. The importance of reaching the limit of warming to 1.5°C in the context of the impact on food security is argued, and a comparison of current climate impacts and the 1.5°C scenario on it is made. The results of the impact of major climate changes on food security and agriculture are analysed. The scenarios of climate change, their characteristics and impact on the ecosystem of food security are revealed. The author’s definition of the food security ecosystem and its basic principles are presented. Potential climatic threats to the food security ecosystem are identified. Originality. The impact of climate change on global food security is substantiated, which, unlike existing approaches, allows for a comprehensive assessment of changes and their impact on the formation of food systems in different periods. The substantiation of the impact of climate change on key aspects of food security has been further developed, which contributes to the development of more sustainable and effective management solutions in this area. Practical value. The conclusions drawn regarding the directions of adaptation of food systems to climate change can be used by actors of the food security ecosystem in practical activities. Assessment of the impact of climate factors allows identifying challenges and proposing measures to increase the sustainability of agriculture and ensure food security. Key words: geopolitical risks, global challenges, economic development, food crises, food security, determinants of food security, agriculture, climate change, global warming, renewable energy sources, adaptation of food systems, food security ecosystem.